PROFIL KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS IV DI GUGUS 2 KECAMATAN PABUARAN KABUPATEN SUBANG - Rayi Siti Fitriani; Hany Handayani; Yudi Bachtiar; Masdi Salimudin Ramdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The government's high attention to literacy and numeracy has been positively responded to with the implementation of the Minimum Competency Assessment program that measures these abilities. It is hoped that this AKM will serve as a foundation for producing individuals who can compete globally in the 21st century. The AKM not only encompasses conceptual understanding but also assesses other mathematical abilities. This research aims to determine the profile of mathematical understanding abilities of fourth-grade students in Cluster 2 of Pabuaran District, Subang. The type of research used is quantitative descriptive analysis, with the research instrument employing test questions that represent all indicators of mathematical understanding. Based on the data analysis results, it can be concluded that students' understanding of mathematical concepts, in general, is still low. On the indicator of restating concepts, all students only reached the sufficient category with scores below 69.99. For the category of classifying objects, students were in the good category with scores between 70 and 84.99. However, in the ability to identify the properties of operations or concepts, all students fall into the very low category with scores below 39. The lowest score is in geometry and measurement, while the highest is in numbers. In the indicator linking various concepts, students fall into the low and sufficient categories. Students achieve a sufficient category in number content and uncertainty data. In the ability to develop necessary and sufficient conditions, students are in the very low category. The highest mathematical understanding score was achieved by SDN Margajaya at 56.08, which falls into the sufficient category, while four other schools are in the low category.